2008
DOI: 10.1073/pnas.0804761105
|View full text |Cite
|
Sign up to set email alerts
|

A triallelic system of S5 is a major regulator of the reproductive barrier and compatibility of indica–japonica hybrids in rice

Abstract: Hybrid sterility is a major form of postzygotic reproductive isolation. Although reproductive isolation has been a key issue in evolutionary biology for many decades in a wide range of organisms, only very recently a few genes for reproductive isolation were identified. The Asian cultivated rice (Oryza sativa L.) is divided into two subspecies, indica and japonica. Hybrids between indica and japonica varieties are usually highly sterile. A special group of rice germplasm, referred to as wide-compatibility vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
246
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(256 citation statements)
references
References 38 publications
3
246
0
7
Order By: Relevance
“…Regarding the reproductive barrier in rice, causal genes were cloned in an allelic interaction case: heterozygotes of Indica allele S5-i and Japonica allele S5-j at the S5 locus induce embryo-sac semi-sterility caused by partial abortion of female gametes carrying the Japonica alleles. Chen et al (2008) sequence level. Chen et al (2008) did not explain the molecular mechanism caused by the heterozygous form at the S5 locus.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the reproductive barrier in rice, causal genes were cloned in an allelic interaction case: heterozygotes of Indica allele S5-i and Japonica allele S5-j at the S5 locus induce embryo-sac semi-sterility caused by partial abortion of female gametes carrying the Japonica alleles. Chen et al (2008) sequence level. Chen et al (2008) did not explain the molecular mechanism caused by the heterozygous form at the S5 locus.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 99%
“…Chen et al (2008) sequence level. Chen et al (2008) did not explain the molecular mechanism caused by the heterozygous form at the S5 locus. In another case, causal genes of reproductive barrier in rice, which had been thought to be allelic before, proved to be a complex of two very tightly linked genes.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al, (2008) cloned S5, a major locus for indica japonica hybrid sterility and wide compatibility, using a map-based cloning approach and found that S5 encodes an aspartic protease conditioning embryo-sac fertility and a discontinuous 136-bp deletion. The same aspartic protease was reported in wide-compatible varieties carrying the neutral allele at S5 locus compared to the indica and japonica alleles using S5 multiplex marker system.…”
Section: Wider Compatibility Approachmentioning
confidence: 99%
“…Plants with the S5-n/S5-j (or S5-i) genotype are fully fertile, while plants with the S5-i/S5-j genotype have low fertility. Chen et al (2008) cloned the S5 gene from the wide-compatibility variety 02428 using a map-based cloning approach and characterized its function. The S5 of indica and japonica differ by two nucleotides, resulting in an amino acid difference and thus leading to hybrid F 1 sterility.…”
Section: Introductionmentioning
confidence: 99%